Plan de marketing para posicionar en el mercado a la microempresa “Comercial Caterine” en el cantón La Maná, año 2015-2019 - Valdez Avilés, Betty Silvana (2016)
Catherine trading company located in La Mana is dedicated to selling groceries, liquor and bazaar generally; however the location the lock of advertising, promotions and inadequate distribution of the products on the shelves are factors that have prevented optimally positioned among the population of the canton. Given the above background it was born the idea of this research whose main objective is the design of a marketing plan that allows positioning the Business Enterprise Caterine in La Mana, Cotopaxi province for which methods were used and techniques such as surveys directed towards potential customers of the company as well as an interview with the owner manager; which allowed us to know that there are shortcomings with regard to the distribution and visibility of the products on hangers, also the low level of training and lack of promotions and advertising strategy to publicize their products in La Mana....